Пятнадцатый камень сада Рёандзи - Цветов Владимир Яковлевич (Беларусь, 1989)
Экземпляры: КХ (20101120) / Инвентарный номер: 941995 / Цена: 2.00 / Сис.шифр: 65.9(4/8) / Авт.знак: Ц 27 / ГРНТИ: 11 / ББК: 65.9(5Япо)